Pembuatan Phantom dari Gips Sebagai Pengganti Tulang Manusia dan Bahan Akrilik Sebagai Pengganti Soft Tissue - Muhammad Sofyan (LPPM STIKES Guna Bangsa Yogyakarta, 2017)
Background: Phantom is very important in radiodiagnostic teaching method, especially in the laboratory of radiography. Exposing object in making radiograph have to consider the amount of radiation which is received by the object. In addition, phantoms price are relatively expensive. To resolve this issue, researcher made phantom using gypsum as subtitute material for bone and acrylic for soft tissue.